PENGARUH PEMBERDAYAAN SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN PEGAWAI DI SEKRETARIAT KOMISI PEMILIHAN UMUM KOTA BANDUNG - Iin Endah Setyawati (Program Studi Manajemen, Universitas Al Ghifari, 2021)
Empowerment of human resources is a new approach that began widely used to improve the quality of human resources, thereby improving the quality of human resources in the activity may no longer just a training and development. Human resource development is an attempt to empower the potential possessed by the man himself in the form of competency, authority and responsibility in order to improve quality of care. Based on the results of preliminary research conducted by researchers, found problems relating to the quality of the ministry in Bandung KPU Secretariat staff are not optimal. Judging from the factor of transparency, accountability factors and participatory factors are low. This study aims to analyze the data and information about the empowerment of human resources for quality of service in the General Election Commission Secretariat Bandung. The research method used was survey explanatory that this method not only to explain or describe the empirical facts encountered in the field but also will explain the analysis of the influence of either partially or simultaneously between variables that are the focus of research. Based on the results of the study and discussion of the coefficient of determination (R2) of 0,946, this means that 94,6% variability of the variable quality of service can be explained by the independent variable in this case the desire terms (X1), the trust factor (X2), the confidence factor (X3) credibility factor (X4) accountability factor (X5) and communication factors (X6), which also means that there are influences shared between desire (X1), the trust factor (X2), the confidence factor (X3) credibility factor (X4) accountability factor (X5 ) and communication factors (X6) on the quality of service for the coefficient of determination (R2 = 94,6%) or it can also mean that the influence of variables outside the model that is equal to 1 - R2 = 0,054 (error). Simultaneously revealed that human resource empowerment variables empirically has a major impact on the quality of care Election Commission Secretariat Bandung. This implies that the operational empowerment of human resources is considered very important and strongly support the quality of service in the Election Commission Secretariat Bandung. The findings of the study also found that the variable quality of service at the Secretariat of the Election Commission of Bandung was not only influenced by variables empowerment of human resources per se, but there are other variables that also affect the quality of the service. Kata Kunci : Pemberdayaan Sumber Daya Manusia, Kualitas Pelayanan Pegawai